Osteoarticular tuberculosis cases in the southwest of China: A 9-year retrospective study - Wang, Dong-Mei; An, Qi; Yang, Qing; Liao, Yi; Jian, Yao (Frontiers in Medicine, 2023)
Abstract Background: Osteoarticular tuberculosis (TB) is an uncommon form of extrapulmonary TB. In this study, we analyzed the epidemiological characteristics, common sites, and drug resistance profile of osteoarticular tuberculosis (TB) infections in southwest China. Methods: A total of 3254 cases clinically diagnosed with osteoarticular TB infections between 2013 and 2021 were retrospectively analyzed. Patient demographic and clinical characteristics were collected. Drug sensitivity testing was performed using the microporous plate ratio method. Chi-square analysis was used to analyze the rate and trend of mycobacterial isolates. Results: Among 3254 patients, 1968 (60.5%) were males, and 1286 (39.5%) were females, ranging from 1 to 91 years old with an average age of 42 ± 19.3. Furthermore, 2261 (69.5%) had spinal TB, mainly thoracic (815, 36 %) and lumbar (1080, 48 %); joint TB was found in 874 cases (26.9 %), mainly in the knee (263, 30 %) and hip (227, 26 %); spinal & joint TB in 119 cases (3.7 %). Drug susceptibility tests were performed on 241 strains of MTB isolated; 70 strains (29.0%) were resistant to at least one drug, and MDR-TB and XDR-TB accounted for 7.1% and 1.2%, respectively. Conclusions: The osteoarticular TB in Southwest China mainly affected middle-aged young men with poor nutritional status. Patients from ethnic minority areas also accounted for a large proportion. Spinal TB is prone to occur in the lumbar and thoracic vertebrae, and joint TB is prone to occur in the lower limb joints. Also, TB cases have shown an increasing trend in the past nine years, and drug resistance increased.